Field Constraints in the adoption of happy seeder technology - Singh, Iqbal; Grover, Jagdish (Indian Farming, 2017)
The major challenge today is to increase the productivity of foodgrains to meet the growing food demand without any adverse environmental impact. In the combine harvested areas, managing heavy loads of rice residues is the major issue. Farmers generally burn rice residue prior to wheat sowing as the cheap and easy option for residue management, but burning leads to several problems such as soil and environmental degradation. The Happy Seeder technology provides an alternative to burning for managing rice residues. The Happy Seeder combines stubble mulching and seed-cum-fertilizer drilling into a single passes.